School dropout in South Africa: The synopsis of its accumulative social, economic, and political effects - Adetiba, Toyin (ARKA INSTITUTE, 2024)
This study explores the synopsis of the accumulative effects of school dropout in South Africa. Primarily attending school until full completion is highly beneficial to individuals and the society, it brings about an upward movement in skills development, crime reduction, better health, and an increased sense of self-confidence. Contrariwise, dropping out of educational and training system often limits individual’s range of possibilities in life. In South Africa, retaining students in school until they graduate from primary or secondary school has become a big challenge to educational policy makers, thus, reflecting the inadequacy of the quality or quantity of the system. Using qualitative method of approach and ecological model, adopted from Bronfenbrenner, this work believes that school dropout is based on the interrelationships between individual learners and multiple systems connected to them which in turn affects the country socially, economically, and politically. The paper concluded that policy makers and education specialists should work together to implement a successful education system suitable for a new generation of students in meeting their challenges of modern globalized world while fostering social mobility and economic growth and reducing the inequitable distribution of societal resources.